THE MICROENTERPRISING SIZE AND ACCEPTANCE OF ISLAMIC HEALTH INSURANCE (TAKAFUL) IN NORTHWESTERN NIGERIA - Mansur Ahmed Kazaure; Addul Rashid Abdullah (Bank Indonesia, 2019)
Application of Theory of Planned Behavior (TPB) in Islamic Health Insurance (takaful) acceptance revealed mixed findings. Hence, the need for a moderating variable to explain the conflicting results. This paper examines the moderating role of size of microenterprise among the TPB variables. To achieve this end, quantitative methodology adopted through distribution of research questionnaires among the participants of the study. Results indicate that attitude, social influence, perceived behavioral control and size of microenterprises significantly influence Islamic Health Insurance (takaful) acceptance intention among microenterprises in northwestern Nigeria. The findings also revealed that size of microenterprise moderates the effect of social influence on Islamic Health Insurance acceptance intention, but it failed to moderate the influence of attitude and perceived behavioral control on Islamic Health Insurance acceptance intention in same context. It implied that size of microenterprises does not matter most in Islamic Health Insurance acceptance; nonetheless, the finding contributes to the Theories of Reasoned Action and Planned Behavior as it provides evidence on the significant moderating role of size on the effect social influence on Islamic Health Insurance acceptance intention among microenterprises.